Exploration of information literacy, technological pedagogical and content knowledge and technological integration self-efficacy abilities of preservice chemistry teachers - Sutoyo, Suyatno; Susantini, Endang; Setiawan, Beni; Allamin, Sophia; Aris, Sharipah Ruzaina Syed (Edelweiss Applied Science and Technology, 2025)
Teachers’ competence to master information literacy and integrate technology into the learning process is essential in the era of the industrial revolution. The purpose of this study is to describe the profile of information literacy (IL), Technological Pedagogical and Content Knowledge (TPACK), and Technology Integration Self-Efficacy (TISE) abilities of preservice chemistry teachers. This study employed a survey research method involving 70 preservice chemistry teachers in the Study Program of Chemistry Education at the State University of Surabaya, all of whom had completed an educational internship course. Data were collected through information literacy ability tests, TPACK, and TISE questionnaires. The data were analyzed using both descriptive and correlation analyses. The results indicated that the three research instruments demonstrated high validity and reliability. The preservice chemistry teachers’ IL, TPACK, and TISE abilities were categorized as high, with average scores of 79.47, 80.86, and 80.07, respectively. Additionally, the study found positive and significant correlations between IL and TPACK, IL and TISE, as well as between TPACK and TISE among preservice chemistry teachers. The findings imply that IL, TPACK, and TISE are crucial competencies that need to be developed in preservice chemistry teachers to enhance their overall teaching competence.